EFFECTIVE STRATEGIES FOR CONDUCTING WRITING CLASSES FOR ESL STUDENTS - Khusomiddinov Boboyor Nurmat o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Teaching writing to English as a Second Language (ESL) students can be both rewarding and challenging. In this article, we explore practical techniques to enhance ESL students’ writing skills. By understanding planning, emphasizing strong sentences, and fostering creativity, educators can create engaging and effective writing classes. We also discuss the importance of collaboration, formal vs. informal writing, and provide valuable resources for further exploration.